Solubility of Edible Films from Amaranth Flour Enzymatic Hydrolyzate Modified with Dialdehyde Starch - Mokrejs, P.; Hrncirik, J.; Janacova, D.; Vasek, V.; Cermak, R. (Asian Journal of Chemistry, 2010)
The objective of the work is to prepare biodegradable and edible films based on Amaranth flour starch-protein hydrolyzate and evaluate the effect of chemical and physical modifications on solubility properties of films. Films were prepared by casting a 14 % (w/w) water solution of hydrolyzate containing 20 % (per hydrolyzate dry matter) glycerol and 0, 1 or 5 % (per hydrolyzate dry matter) additions of dialdehyde starch. After thermal exposure of films at 65 or 95 ºC (for 6 or 48 h) film solubility tests were performed in water at 6 or 37 ºC. It was found that chemical modification (added dialdehyde starch) and physical modification (thermal exposure) of films allows to markedly altering their water solubility. Results of water solubility tests can serve to practically utilizing starch-protein hydrolyzate of Amaranth flour for producing biodegradable packaging materials (foils, coatings) to be employed in the food industry, cosmetics or agriculture.